English Learning Management in Improving Students’ Writing Skills - Mujahidin, Irfan; Asyaari, Asyaari; Sugiharto, Sapto; Sugiarta, I Wayan Arif; Shalabi, Mohamed Salah Elsayed (Thawalib: Jurnal Kependidikan Islam, 2025)
The lack of attention to writing skills in managing English learning at junior high schools has become a significant concern, even though these skills are crucial in supporting students’ academic competence. This research aims to analyze the management of writing instruction at Nihayatul Amal Rawamerta Junior High School, Karawang, and to identify innovative solutions to overcome students’ difficulties and improve the quality of their writing skills. This study applied a qualitative case study approach with data collected through interviews, observations, and documentation. The data analysis was conducted through condensation, presentation, and conclusion drawing. The findings indicate that English learning management at Nihayatul Amal Rawamerta Junior High School is implemented systematically through planning, organizing, evaluation, and problem-solving. In the planning stage, teachers prepare annual programs, semester programs, and detailed lesson plans to support the enhancement of students’ writing skills. The organizing stage includes determining objectives, selecting methods, and designing relevant learning materials. The implementation stage applies the discovery learning model with a scientific approach to foster students’ active involvement in exploring and discovering writing concepts. The evaluation stage assesses attitudes, knowledge, and writing performance. Several challenges are identified, including limited vocabulary, grammatical weaknesses, and inadequate facilities. The solutions suggested include increasing reading activities, providing continuous writing practice, and giving constructive feedback. Conclusion: English learning management is systematically carried out through planning, organizing, implementation, and evaluation to enhance students’ writing skills in an active, creative, and optimal manner.